2006
DOI: 10.1590/s0100-41582006000100001
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de danos pós-colheita em pêssegos no mercado atacadista de São Paulo

Abstract: Quantification of post harvest damage in peaches in São Paulo's wholesale marketThe occurrence of post harvest disturbances in peaches (Prunus persicae) is an important cause of product depreciation during its commercialization. The objectives of this paper were to quantify and characterize the post harvest damage in peaches at CEAGESP, the biggest wholesale market in the State of São Paulo. The incidence of damages was assessed at 1% of commercialized fruits in CEAGESP, at each evaluation date during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 3 publications
(7 reference statements)
0
7
0
17
Order By: Relevance
“…Martins et al (2006) quantificaram esses danos no mercado atacadista de São Paulo. Nesta pesquisa, os gêneros fúngicos de ocorrência mais freqüente foram Monilinia (podridão-parda), Rhizopus (podridão-mole) e Cladosporium.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Martins et al (2006) quantificaram esses danos no mercado atacadista de São Paulo. Nesta pesquisa, os gêneros fúngicos de ocorrência mais freqüente foram Monilinia (podridão-parda), Rhizopus (podridão-mole) e Cladosporium.…”
Section: Introductionunclassified
“…Nesta pesquisa, os gêneros fúngicos de ocorrência mais freqüente foram Monilinia (podridão-parda), Rhizopus (podridão-mole) e Cladosporium. Constatou-se que as variedades comercializadas em maior volume, Aurora, Chiripá, Dourado, Douradão, IAC e Ouromel, não apresentaram diferenças significativas na incidência de doenças (Martins et al, 2006). De acordo com Almeida (2006), os pêssegos 'Douradão'foram eleitos como os melhores pelos atacadistas, pois apresentaram as melhores características qualitativas.…”
Section: Introductionunclassified
“…Physical damage to fruit is important for pathogen penetration, especially for fungi that cause postharvest rots (Agrios, 2005). Postharvest damage during marketing can cause up to 50% loss of stone fruits (Martins et al, 2006). Studies carried out in a wholesale market in Brazil showed a correlation between mechanical damage and postharvest diseases in stone fruits (Martins et al, 2006;Amorim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Postharvest damage during marketing can cause up to 50% loss of stone fruits (Martins et al, 2006). Studies carried out in a wholesale market in Brazil showed a correlation between mechanical damage and postharvest diseases in stone fruits (Martins et al, 2006;Amorim et al, 2008). In Brazil, diseases are the main cause of price reduction among all postharvest damage in peaches.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, sendo um fruto climatérico e de alta perecibilidade, várias desordens de natureza biótica e abiótica são responsáveis pela diminuição da produção e/ou qualidade dos pêssegos no campo e após a colheita. Os distúrbios pós-colheita, podendo ser de natureza física, fisiológica e patológica, são importantes causas de desvalorização do produto durante a comercialização e têm motivado a realização de vários trabalhos sobre a quantificação de danos em pêssegos comercializados na CEAGESP (ABREU, 2006;GUTIERREZ, 2005;MARTINS et al, 2006). Levantamentos realizados nas safras 2001 e 2002 mostraram que entre 4,9 e 44,5% dos pêssegos apresentavam algum tipo de dano pós-colheita, e que frutos doentes eram a segunda maior causa da desvalorização do produto, perdendo apenas para a ocorrência de injúrias mecânicas.…”
Section: Revisão Bibliográficaunclassified